53. CHARACTERISTICS OF POSTOPERATIVE HYPOCALCEMIA FOLLOWING THYROID SURGERY AT 175 MILITARY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the characteristics of postoperative hypocalcemia, clinical symptoms, and associated risk factors following thyroid surgery at Military Hospital 175.Subjects and Methods: A cross-sectional descriptive study combined with a prospective approach was conducted on 44 patients undergoing thyroid surgery at Military Hospital 175 from May 2022 to September 2024.Results: Among 44 patients, the mean age was 46.3 ± 11.2 years, with females accounting for the majority (79.55%). The majority of patients did not experience hypocalcemia (68.18%), while transient hypocalcemia occurred in 22.73%, and permanent hypocalcemia was observed in 9.09%. Common clinical symptoms included paresthesia (63.64%), tetany (36.36%), cardiac arrhythmia (9.09%), and laryngeal spasm (4.55%). Major risk factors included total thyroidectomy (65.91%), parathyroid gland injury (36.36%), and bleeding or neck edema (15.91%). Significant associations were found between risk factors such as the type of surgery and parathyroid gland injury with postoperative hypocalcemia (p
Keywords: Hypocalcemia; thyroid surgery; parathyroid gland injury.